BRIDGING THE DIGITAL LITERACY GAP: THE ROLE OF PUBLIC EDUCATION IN BUSINESS LICENSING SERVICES IN SAMARINDA - Agus Setiawan; Aji Ratna Kusuma; Saipul Saipul (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aims to analyze the quality of Business Identification Number (NIB) issuance services and to evaluate the role of public education in enhancing the digital literacy of business actors. The research employs a qualitative descriptive approach with data collected through in-depth interviews, direct observation, and document studies. Informants were purposively selected, including leaders, functional officers, service staff, and business actors as users. Data analysis was conducted using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results indicate that the overall quality of services is good, with simple procedures, clear requirements, and responsive staff, especially for applicants with limited digital literacy. However, limitations in procedure socialization, reliance on the centralized OSS system, and technical disruptions remain challenges. Variations in applicants’ digital literacy levels affect service effectiveness. The study highlights the importance of public education as a strategy to improve digital literacy through procedural socialization, user assistance, and digital-based training. These improvements are expected to strengthen service reliability, make the licensing process more inclusive, effective, and sustainable, and support ease of doing business.